Bioactive Secondary Metabolites to Combat Diabetic Complications: Evidenced from in Silico Study (Bangladesh Pharmaceutical Journal, 2023)
Diabetes mellitus (DM) is a condition characterized by excessive blood sugar levels, which have recently reached the level of a pandemic. There are various side effects of each drug to treat this condition. Molecular docking is a modern concept for computer-aided drug designing. Using this technique several potential antidiabetic phytocompounds are evaluated against three target receptors including GLUT-3, PPARγ and α-amylase related to DM. These compounds' ADMET and drug-likeliness characteristics have also been assessed to determine potential drug candidacy. Most of the compounds exhibited magnificent binding affinity against these targets, especially compounds 30 and 27 have shown great affinity against GLUT-3 with values of -11.2 and -10.2 Kcal/mol respectively. Where compound 37 has the highest binding affinity (-9.1 Kcal/mol) against PPARγ. Also, with values of -11.6 and -10.8 Kcal/mol respectively compounds 38 and 12 notably bind with α-amylase. Moreover, all of these compounds have magnificent results on ADMET and drug-likeliness studies, in particular, compound 29 has shown high affinity against all of these receptors, explored 0.55% bioavailability score, no toxicity and high absorptivity. Although these compounds have undergone a preliminary drug discovery study, more research must be done to determine their precise mechanism of action against DM.Bangladesh Pharmaceutical Journal 26(2): 167-184, 2023 (July)